Propagação de modificações em documentos XML para bancos de dados relacionais - Schuch, Regis Rodolfo (2014)
Many environments require the storage of XML data (eXtensible Markup Language) in RDB (Relational Databases). In such cases, in addition to mapping the XML schema and data to tables in the RDB, it is also necessary to update the RDB once the XML data are modified. To perform the updating process, this work proposes the DBUpdater (Database Updater), a component that detects and propagates XML changes to a RDB. The content change propagation from XML documents to the RDB is not a task whose execution is straightforward. Due to the absence of a means to track the XML data, a mechanism is needed to generate XML keys which allows the XML data relate to the tuples in the relational tables. The main contributions of this work are: the change detection based on diff algorithms; the generation and assignment of identifiers for the XML nodes; the generation of keys for the XML data based on the identifiers assigned to the nodes; and the definition of equivalence between the detected change operations in relation to the database update operations. This proposal is part of X2Rel (XML to Relational) framework, an environment for storing, maintaining and querying heterogeneous XML data in RDB.